O direito humano à água potável e a resolução de conflitos ambientais pelo Ministério Público - Barcellos, Rodrigo Alves (Universidade Federal do Tocantins, 2018)
The study seeks to identify the reality of environmental disputes involving the human right to water, by presenting mechanisms for solving conflicts, through the work of the Public Prosecution Service. As a specific clipping, the dissertation addresses the alarming situation of the water bodies of the Rio Formoso hydrological basin, in the southwest region of the state of Tocantins. The theoretical background of the study was based on the contributions of authors and researchers in the areas of environmental law, geography, ecology and agronomy. The methodological basis was based on bibliographical, statistical, documental and procedural analysis. It was recognized that access to justice is not access to the Judiciary, but to the solution of the litigation with agility, efficiency, adequacy, professionalism and social commitment. The right to clean water involves a question of environmental justice and the body constitutionally mandated to defend the democratic regime must offer alternatives to ensure a dignified life for all, a supreme value of a society committed to the peaceful resolution of conflicts, according to the preamble of the Constitution. After studying the principles of Environmental Law and the management of water resources, the paths of excessive litigiousness that overload the Brazilian courts to identify the need to expand knowledge about the modern theory of conflict as a way of inspiring the action of the members of the Public Prosecutor's Office to adopt, preferably, self-composed methods of conflict resolution.